PEMANFAATAN (ARTIFICIAL INTELLIGENCE) AI; PENGEMBANGAN MODEL DIGITAL SPIRITUAL CONSTRUCTIVISM DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA MUHAMMADIYAH 4 YOGYAKARTA - Aisyah Ali, Tria Bella; Nabila, Childan; Setiawati, Erlin Putri; Saputri, Alya Zalikhah; Putra, Lovandri Dwanda (Penerbit Widina, Widina Media Utama, 2026)
The use of artificial intelligence (AI) in the teaching and learning of Islamic Religious Education (PAI) is increasingly becoming a necessity in the digital era, but it must be maintained to ensure it aligns with the values of faith and morals of students. This study seeks to investigate the application of AI in PAI education at the high school level through the formulation of the Digital Spiritual Constructivism model. This model places particular emphasis on teachers' understanding, delivery methods, spiritual aspects, and ethics in the use of AI. This study used qualitative methods through in-depth interviews with PAI teachers at SMA Muhammadiyah 4 Kotagede, and the results were then analyzed thematically. The research findings indicate that AI, particularly through application-based digital learning platforms, can increase student engagement and make the learning process more efficient, especially for the digital generation. However, the use of AI has not fully integrated aspects of spiritual reflection and in-depth religious understanding. Teachers have a crucial role as facilitators in guiding the use of AI to remain in line with Islamic values, such as honesty, responsibility, and digital etiquette, and preventing the misuse of AI that could diminish students' academic honesty and religious depth. The research conclusion shows that the development of the Digital Spiritual Constructivism model must be directed by combining technology, the principles of constructivism learning, and Islamic values in a balanced manner so that AI can truly become an effective, meaningful, and spiritually based Islamic education learning tool.ABSTRAKPemanfaatan kecerdasan buatan (Artificial Intelligence/AI) dalam proses belajar mengajar Pendidikan Agama Islam (PAI) semakin menjadi kebutuhan di tengah era digital, tetapi harus tetap dijaga agar sesuai dengan nilai-nilai keimanan dan akhlak peserta didik. Penelitian ini bertujuan untuk mengkaji penggunaan AI dalam pembelajaran PAI di tingkat SMA melalui pengembangan model Digital Spiritual Constructivism. Model ini memberi perhatian khusus pada pemahaman para guru, cara penyampaian materi, aspek spiritual, serta etika dalam penggunaan AI. Penelitian ini menggunakan metode kualitatif dengan cara wawancara mendalam pada para guru PAI di SMA Muhammadiyah 4 Kotagede, lalu hasilnya dianalisis secara tematik. Temuan penelitian menunjukkan bahwa AI, terutama melalui platform pembelajaran digital berbasis aplikasi, mampu meningkatkan keterlibatan siswa dan membuat proses belajar lebih efisien, terutama bagi kalangan generasi digital. Namun, penggunaan AI belum sepenuhnya mengintegrasikan aspek refleksi spiritual dan pemahaman keagamaan yang mendalam. Para guru memiliki peran penting sebagai fasilitator untuk mengarahkan penggunaan AI agar tetap sesuai dengan nilai-nilai Islam, seperti kejujuran, tanggung jawab, dan adab digital, serta mencegah penggunaan AI secara salah yang bisa mengurangi kejujuran akademik dan kedalaman keagamaan siswa. Kesimpulan penelitian menunjukkan bahwa pengembangan model Digital Spiritual Constructivism harus diarahkan dengan menggabungkan teknologi, prinsip konstruktivisme pembelajaran, dan nilai-nilai Islam secara seimbang, agar AI benar-benar bisa menjadi sarana pembelajaran PAI yang efektif, bermakna, dan sesuai dengan nilai spiritual.